ANALISIS PEMASARAN UDANG PUTIH (Litopenaeus vannamei) DI KELURAHAN KUALA SAMBOJA KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Leni Faizah; Nurul Ovia Oktawati; Fitriyana (2339-1324, 2021)
This research was aimed to determine the marketing channels, costs, margins, and farmer's share of white shrimp (Litopenaeus vannamei) in Kuala Samboja Village, Samboja Sub-district, Kutai Kartanegara Regency. The research was conducted in Kuala Samboja Village, Samboja Sub-district, Kutai Kartanegara Regency. The samples used in the study were 15 fishermen and 2 white shrimp (Litopenaeus vannmei) traders. The sampling method used was purposive sampling and snowball sampling. The results showed that: there are 2 marketing channels for white shrimp (Litopenaeus vannamei), namely the level zero (0) marketing channel and the level two (2) marketing channel with 2 types; meanwhile the marketing costs at the level zero (0) marketing channel is Rp. 392/kg, at the level two (2) type 1 marketing channel is Rp. 3.043/kg, and at the level two (2) type 2 marketing channel is Rp. 2,487/kg. The total marketing margin is at level two (2) marketing channel with Rp. 67,500/kg and Rp. 36,700/kg. And the highest farmer's share is at the zero level marketing channel (0) which is equal to 100% and is the most efficient marketing channel. Keywords: Marketing Channels, Costs, Margins, Farmer's Share, Kuala Samboja